Consequences of estuarine sand dredging and dumping on the Urdaibai Reserve of the Biosphere (Bay of Biscay): the case of the “Mundaka left wave” - Cearreta, A.; Monge-ganuzas, M.; Iriarte, E. (Journal of Iberian Geology, 2008)
In the spring of 2003, 240,000 m3 of sand were dredged from the main channel of the lower Oka estuary (Urdaibai Reserve of the Biosphere) and dumped on the southern area of Laida beach located at the estuary mouth. After few months, strong erosion of the deposited sediments occured as a consequence of the northwards migration of the final meander of the main estuarine channel before it reached the estuary inlet. At the same time, the estuarine inlet abandoned its original position near the rocky western margin and migrated eastwards cutting and eroding the sandy ebb delta (Mundaka sand bar). This caused a change in the way the incident wave broke as it reached the shallow water of the ebb tidal delta and beach and made surfing impossible under the same optimal conditions previously enjoyed due to the production of a wave that gradually broke from right to left as it reached shallow water, the so called “Mundaka left wave”. As a consequence, the Billabong Pro surf championship was cancelled in 2005. This paper describes the results obtained during a study of the outer estuary carried out during the period May 2005-April 2006 to characterize the processes operating on the most dynamic area of the estuary throughout the year and to evaluate the influence that the anthropogenic activities in the estuary had on the wave characteristics. No corrective measures were taken in the outer estuary during the study period and the environment recovered its normal morphological features naturally. This natural restoration it is hoped will be more stable, long lasting and reliable to ensure the continuing future of the “Mundaka left wave”.